The Influence of Internal Communication and Motivation on The Improvement of Employee Performance at Puri Pandawa Resort, Badung Regency, Bali - Putriati Desliana Ina Ate; Poppy Indrihastuti; Nur Ida Iriani; Fitria Setyaningrum (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study was to determine whether there was an influense of internal communication and motivation on improving employe performance at Puri Pandawa Resort. The type of research used was quantitative. The determination of the research sample was 30 respondents. The data collection steps used by the researcher were questionnaires. The data analysis techniqui was multiple linear regression analysis using the SPSS program. The results of the study proved that internal communication had a negative and insignificant effect on improving employee performance at Puri Pandawa Resort Badung Regency, Bali t count (-0.049), motivation had a positive and significant effect on imploying employee performance at Puri Pandawa Resort Badung Regency, Bali t count (5.857). These results prove that motivation has a positive and significant effect on improving employee performance at Puri Pandawa Resort Badung Regency, Bali.